2018
DOI: 10.1021/acs.est.8b00425
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Polycyclic Aromatic Hydrocarbons and Formation of Environmentally Persistent Free Radicals on Modified Montmorillonite: The Role of Surface Metal Ions and Polycyclic Aromatic Hydrocarbon Molecular Properties

Abstract: This paper presents the transformation of PAHs (phenanthrene, anthracene, benzo[a]anthracene, pyrene, and benzo[a]pyrene) on montmorillonite clays that are modified by transition-metal ions [Fe(III), Cu(II), Ni(II), Co(II), or Zn(II)] at room temperature (∼23 °C). The decay of these PAHs follows first-order kinetics, and the dependence of the observed rate constants ( k, day) on the presence of metal ions follows the order Fe(III) > Cu(II) > Ni(II) > Co(II) > Zn(II). The values of k show reasonable linear rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(85 citation statements)
references
References 53 publications
6
79
0
Order By: Relevance
“…These values are typical of free organic radicals. All spectra are consistent with the characteristics of benzo[a]pyrene-EPFR (Jia et al 2018). According to previous studies, free radicals with g-factor lower than 2.0030 are considered as carbon-centered radicals; the g-factor of oxygen-centered radicals is greater than 2.0040; and free radicals with g-factors in the range of 2.0030-2.0040 are mixed radicals of carbon-and oxygencentered radicals (Zhu et al 2019).…”
Section: Formation Of Environmentally Persistent Free Radicals Duringsupporting
confidence: 85%
See 2 more Smart Citations
“…These values are typical of free organic radicals. All spectra are consistent with the characteristics of benzo[a]pyrene-EPFR (Jia et al 2018). According to previous studies, free radicals with g-factor lower than 2.0030 are considered as carbon-centered radicals; the g-factor of oxygen-centered radicals is greater than 2.0040; and free radicals with g-factors in the range of 2.0030-2.0040 are mixed radicals of carbon-and oxygencentered radicals (Zhu et al 2019).…”
Section: Formation Of Environmentally Persistent Free Radicals Duringsupporting
confidence: 85%
“…The preparation of benzo[a]pyrene-contaminated soils was previously described (Jia et al 2018). Briefly, 1 g of soil sample was mixed with 1 mL of acetone solution containing 500 mg L −1 of benzo[a]pyrene.…”
Section: Preparation Of Soils Contaminated By Benzo[a] Pyrenementioning
confidence: 99%
See 1 more Smart Citation
“…Benzo [a]pyrene-spiked soil samples were prepared with previously described methods (Jia et al 2018;Zhao et al 2017). Samples included three soils: bauxite soil, fluvo-aquic soil and chernozem soil, and pure components: montmorillonite, humic acid and quartz sands.…”
Section: Soil Sample Collection and Benzo[a]pyrene-spiked Sample Prepmentioning
confidence: 99%
“…Previous studies suggested that the g -factors less than 2.00300 were typical for (C-centered) free radicals 23,24 . Oxygen-centered (O-centered) free radicals usually possess the g -factor larger than 2.00400, such as semiquinone or phenoxyl radicals 25,26 . And radical signals with g -factors of 2.00300–2.00400 are attributed to a combination of the C-centered and O-centered EPFRs 26 .…”
Section: Resultsmentioning
confidence: 99%